1999
DOI: 10.1016/s0002-9440(10)65445-4
|View full text |Cite
|
Sign up to set email alerts
|

Histological Damage in Chronic Hepatitis C Is Not Related to the Extent of Infection in the Liver

Abstract: It has not been completely elucidated whether the liver injury induced by the hepatitis C virus (HCV) is due to direct cytopathic damage or to an immune-mediated response against HCV-infected hepatocytes. In this work, we have determined the percentage of HCV-infected hepatocytes, the histological activity index, and the viremia levels in chronically HCV-infected patients with different grades of liver injury to investigate any possible correlation between them. For that purpose, liver biopsies from 27 patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
30
0
1

Year Published

2001
2001
2007
2007

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 53 publications
(34 citation statements)
references
References 24 publications
3
30
0
1
Order By: Relevance
“…Finally, no differences in either liver enzyme levels or liver damage were found between patients with and those without detectable levels of HCV RNA in serum, indicating that, as occurs in patients with classical chronic HCV infection (16,17), liver damage in occult HCV infection does not depend on HCV RNA serum levels.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…Finally, no differences in either liver enzyme levels or liver damage were found between patients with and those without detectable levels of HCV RNA in serum, indicating that, as occurs in patients with classical chronic HCV infection (16,17), liver damage in occult HCV infection does not depend on HCV RNA serum levels.…”
Section: Discussionmentioning
confidence: 79%
“…Genomic HCV RNA was detected as described previously (7,9,16), with a cRNA probe labeled with digoxigenin 11-UTP obtained by in vitro transcription of pC5ЈNCR, which contains the complete 5Ј noncoding region of the HCV genome. The percentage of infected cells was determined by visual inspection, and at least 2,000 cells from each liver section were counted.…”
Section: Patientsmentioning
confidence: 99%
“…39 Kinetic analysis of viral turnover in patients indicated that HCV infection is a highly dynamic process with a short half-life of viral particles and HCV-infected cells. 40 It has been calculated that the daily turnover of HCV-infected cells may be as high as 13% to 25%.…”
Section: Discussionmentioning
confidence: 99%
“…De Moliner et al reported an association between the levels of viremia and the amount of virus in the liver but no relationship between viral load and ALT level, genotype, or histological diagnosis (2). Likewise, Rodriguez et al demonstrated a significant association between the proportion of infected hepatocytes and viral load but no relationship with the histological activity index (18). Fanning et al, however, noted a weak association (r s ϭ 0.26) between viral load and degree of inflammation but no relationship between viral load and degree of fibrosis or ALT level (4).…”
Section: Discussionmentioning
confidence: 99%
“…The majority of studies have not been able to find any relationship between HCV RNA concentrations and liver fibrosis (2,4,18). However, in a multivariate logistic analysis, Iijima et al noted a significant association between deterioration of the histological stage and amount of HCV viremia though the odds ratio was extremely low (8).…”
mentioning
confidence: 99%